Demodex Species Frequency and Risk Factors in Patients With Rheumatoid Arthritis - Hatice YAZISIZ,; Yeşim ÇEKİN,; İlhan SEZER,; Feyzi BOSTAN,; Fatma Gülsüm KOÇLAR, (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the presence of Demodex species in rheumatoid arthritis (RA) patients, to identify the risk factors for developing Demodex infestation, and to determine the effect of immunosuppressant drugs on Demodex mite infestations. Patients and methods: The study included 93 RA patients (16 males, 77 females; mean age 53.3±11.3 years; range, 27 to 83 years) and 76 healthy controls (19 males, 57 females; mean age 50.3±13.9 years; range, 19 to 86 years). Specimens were collected from face skin by using standardized sur- face skin biopsy. Demodex infestation was considered for ≥5 living parasites/cm2 of skin while Demodex mite presence was defined as any Demodex larvae, adults, or eggs found in the specimen. Results: The frequencies of Demodex mite presence were 44% for the RA patients and 15.7% for the healthy controls (p<0.001). The rates of Demodex infestation were similar between the two groups (18.3% versus 7.9%, p=0.054). There were no statistically significant differences between the groups regarding skin type, skin care, epilation, body washing, use of a moisturizer, personal towel use, the number of residents at home, or whether there were pets at home or in proximity. Itching in eyes was higher in RA patients, but the frequency of other skin symptoms was not differ- ent from healthy controls. Logistic regression analysis indicated that the diagnosis of RA was an independent risk factor for Demodex mite presence in this study population. Disease activity and duration, use of corticosteroids, conventional disease-modifying anti-rheumatic drugs (DMARDs) and biological DMARDs were not effective factors on Demodex mite presence in RA patients. Conclusion: Although Demodex mite presence was 3.5-fold higher in RA patients, the rate of Demodex infestation was similar to that of healthy controls.